Simulation based analysis on ways to improve the factory performance - Xie, Zhiyu (2014)
An effective production strategy would lead to efficient production line performance as well as increased profit. However, there is no fixed or generalized solution. In this project, the author treat the n-job, two-stage hybrid flow line problem with 2 different machines in the first station and 7 identical machines in the second station. The objective for this project is to reducing the total cost. The author researched the ways to improve a company’s performance by reducing the total cost from four different aspects (Production batches, transfer batches, dedicated line as well as predetermining a shared product type). After this project, the total estimated saving for company will be S$18988.6 per 42 weeks, which is over 10% of total cost. The research is meaningful and can provide a guide for manufacturing industry.